Low Expression of miR-466f-3p Sustains Epithelial to Mesenchymal Transition in Sonic Hedgehog Medulloblastoma Stem Cells Through Vegfa-Nrp2 Signaling Pathway - Besharat, Zein Mersini; Sabato, Claudia; Po, Agnese; Gianno, Francesca; Abballe, Luana; Napolitano, Maddalena; Miele, Evelina; Giangaspero, Felice; Vacca, Alessandra; Catanzaro, Giuseppina; Ferretti, Elisabetta (Frontiers in Pharmacology, 2018)
High-throughput analysis has improved the knowledge of medulloblastoma (MB), the leading cause of cancer related death in children, allowing a better comprehension of the key molecular pathways in MB pathogenesis. However, despite these advances, 30% of patients still die from the disease and survivors face severe long-term side effects. Cancer stem cells (CSCs) represent a subset of cells that not only drive tumorigenesis, but are also one of the main determinants of chemoresistance. Epithelial mesenchymal transition (EMT) is a hallmark of cancer and up to now few data is available in MB. To give insight into the role of the EMT process in maintaining the mesenchymal phenotype of CSCs, we analyzed the expression of EMT related transcripts and microRNAs in these cells. We firstly isolated CSCs from Sonic Hedegehog (SHH) MB derived from Ptch1 heterozygous mice and compared their expression level of EMT-related transcripts and microRNAs with cerebellar NSCs. We identified two molecules linked to SHH and EMT, Vegfa and its receptor Nrp2, over-expressed in SHH MB CSCs. Inhibition of Vegfa showed impairment of cell proliferation and self-renewal ability of CSCs concurrent with an increase of the expression of the EMT gene, E-cadherin, and a decrease of the EMT marker, Vimentin. Moreover, among deregulated microRNAs, we identified miR-466f-3p, a validated inhibitor of both Vegfa and Nrp2. These results allowed us to describe a new EMT molecular network, involving the down-regulation of miR-466f-3p together with the concordant up-regulation of Vegfa and Nrp2, that sustains the mesenchymal phenotype of SHH MB CSCs.